Investigating key beliefs guiding mothers' dietary decisions for their 2–3 year old. (1st June 2015) - Spinks, Teagan; Hamilton, Kyra
Highlights: Childhood 'healthy eating' and 'discretionary choices' behaviours were investigated. Key beliefs predicted mothers' actions for their child's eating behaviours. The beliefs provide targets for future interventions to promote healthy eating. Abstract: Currently, there is no research in Australia that systematically investigates the underlying beliefs for mothers' decisions regarding their young child's nutritional needs based on current guidelines. We aimed to determine, using a Theory of Planned Behaviour (TPB) belief-based approach, key beliefs that guide mothers' decisions with regards to: (a) providing their child with a wide range of foods from the five food groups ('healthy eating'); and (b) limiting their child's intake of 'discretionary choices' (e.g. lollies). Mothers (N = 197, M age = 34.39, SD = 5.65) completed a main questionnaire either online or on hard copy (paper-based), with a 1-week phone follow-up of the target behaviours (N = 161). Correlations and multiple regression analyses were conducted, and a number of key behavioural, normative, and control beliefs emerged for both healthy eating and discretionary choice behaviours. For healthy eating, mothers identified behavioural beliefs 'improving my child's health' and 'resistance from my child'; normative beliefs 'other family members' and 'spouse/partner'; and control beliefs 'child's food preferences'. For discretionary choices, behavioural beliefs 'maintain consistent energy levels in my child' for intentions, and 'give my child their required nutritional intake'; normative beliefs 'spouse/partner', 'healthcare professionals' and 'friends'; and control beliefs 'child's food preferences' were identified. These findings can inform the development of future intervention programmes aimed at modifying mothers' child feeding practices to encourage healthy eating and limit discretionary choice intake and, ultimately, increase the life expectancy of the current generation of children.